Incorporation of a TGF-β2-inhibiting oligodeoxynucleotide molecular adjuvant into a tumor cell lysate vaccine to enhance antiglioma immunity in mice - Tu, Liqun; Wang, Zhe; Yang, Lei; Sun, Xiaomeng; Yao, Yunpeng; Zhang, Peng; Zhang, Xiaotian; Wang, Liying; Yu, Yongli; Yang, Ming (Frontiers in Immunology, 2023)
Transforming growth factor β2 (TGF-β2), also known as glioma-derived T-cell suppressor factor, is associated with the impairment of tumor immune surveillance. Therefore, blocking TGF-β2 signaling might be a feasible strategy to develop a novel type of adjuvant for glioma vaccines to enhance antitumor immunity. To develop an effective TGF-β2 inhibitor, a TGF-β2 inhibitory oligodeoxynucleotide (TIO3) was designed with sequences complementary to the 3’ untranslated region of TGF-β2 mRNA. In this study, TIO3 was observed to be easily taken up by CD4+ T cells, CD8+ T cells, B cells and Ly6G+ immune cells, resulting in significant inhibition of TGF-β2 expression in various cells and tissues, including cultured GL261 and U251 glioma cells, glioma tissues, and CD4+ and CD8+ T immune cells. TGF-β2 inhibition was associated with MHC-I upregulation, and TIO3 exhibited the ability to upregulate MHC-I mRNA and protein expression in GL261 cells, contributing to the promotion of the recruitment of cytotoxic effector cells to the tumor microenvironment. Thus, a glioma vaccine consisting of a TIO3 adjuvant and glioma cell lysate (TCL) was investigated for its antitumor effects in mouse GL261 glioma prophylactic and therapeutic models. Our in vivo results indicated that TCL+TIO3 significantly prolonged the survival of glioma-bearing mice and induced glioma-speciﬁc immunologic memory. The major mechanisms involved in the protective effects in mice may include the following two aspects. First, TCL+TIO3 triggered the generation of cytotoxic T lymphocytes (CTLs) and activation of NK cells in splenocytes and lymphocytes, including the IFN-γ secreting frequencies of CD4+ and CD8+ T cells, the elevation of CD69 or NKG2D expression in NK cells, and the induction of specific CTLs in glioma-bearing mice. Second, TCL+TIO3 dramatically reduced PD1 expression on CD4+ T, CD8+ T and NK cells in draining lymph node cells, as well as PD-L1 expression in glioma tissues and in Ly6G+ cells in glioma-infiltrating immune cells. In conclusion, TIO3 is a promising adjuvant for enhancing TCL-based vaccines to produce a more vigorous and long-lasting antitumor response by interfering with TGF-β2 expression.